2020
DOI: 10.1016/j.ijporl.2019.109720
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of auditory and language development in the early stages of pre-lingual children post cochlear implantation: A longitudinal follow up study

Abstract: Objectives: The aim of this longitudinal follow-up study was to explore the trajectories of early auditory and language development in Mandarin speaking children younger than 3 years of age following switch-on of their cochlear implants (CIs). Methods: Early auditory and language development was measured longitudinally using the Infant-Toddler Meaningful Auditory Integration Scale (IT-MAIS), which is a commonly used tool for assessing early prelingual auditory development (EPLAD) in children, and the subtest (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Data showed no or very low level of auditory skills preimplant. After 6 months of CI use, these children could achieve a score of about 50∼60% on the IT-MAIS/MAIS (Chen Y. et al, 2016;Lu and Qin, 2018;Li G. et al, 2020) and reach (Chen Y. et al, 2016Lu and Qin, 2018;Li G. et al, 2020) and reach category 4 (i.e., discriminates at least two speech sounds) on the CAPQ (Lyu et al, 2019;Jiang et al, 2020). More than half of the children could achieve category 4 (i.e., vowel perception) and category 5 (i.e., consonant perception) on the MESP test (Zheng et al, 2011;Chen Y. et al, 2016;Guo et al, 2016;Lu and Qin, 2018).…”
Section: Longitudinal Studies On the Development Of Auditory And Speech Perceptionmentioning
confidence: 98%
See 2 more Smart Citations
“…Data showed no or very low level of auditory skills preimplant. After 6 months of CI use, these children could achieve a score of about 50∼60% on the IT-MAIS/MAIS (Chen Y. et al, 2016;Lu and Qin, 2018;Li G. et al, 2020) and reach (Chen Y. et al, 2016Lu and Qin, 2018;Li G. et al, 2020) and reach category 4 (i.e., discriminates at least two speech sounds) on the CAPQ (Lyu et al, 2019;Jiang et al, 2020). More than half of the children could achieve category 4 (i.e., vowel perception) and category 5 (i.e., consonant perception) on the MESP test (Zheng et al, 2011;Chen Y. et al, 2016;Guo et al, 2016;Lu and Qin, 2018).…”
Section: Longitudinal Studies On the Development Of Auditory And Speech Perceptionmentioning
confidence: 98%
“…Data showed no or very low level of auditory skills pre-implant. After 6 months of CI use, these children could achieve a score of about 50∼60% on the IT-MAIS/MAIS ( Chen Y. et al, 2016 ; Lu and Qin, 2018 ; Li G. et al, 2020 ) and reach category 3 (i.e., recognizes environmental sounds) on the CAPQ ( Lyu et al, 2019 ; Chen Y. et al, 2020 ; Jiang et al, 2020 ). About 40∼88% of children reached category 2 (i.e., speech pattern perception) or higher on the MESP test ( Zheng et al, 2011 ; Chen Y. et al, 2016 ; Guo et al, 2016 ; Lu and Qin, 2018 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech production constitutes an essential outcome measure in the assessment of children with CIs. However, there are few studies that have examined speech production in Mandarin-speaking children with CIs, with most published work focussing on expressive vocabulary development and speech intelligibility (Han et al 2007;Li et al 2020). Where studies do report speech production measures in Mandarinspeaking children with CIs, they often show conflicting results and are based on different materials and methods (Chuang et al 2012;Deroche et al 2019;Han et al 2007;Mao, Chen, and Xu 2017;Tseng, Kuei, and Tsou 2011).…”
Section: Introductionmentioning
confidence: 99%
“…everal studies have shown that the use of cochlear implants (CIs) improves the speech perception and language skills of children with hearing loss (Quittner et al, 2004;Spencer & Marschark, 2010;Tomblin et al, 2008;Uhler et al, 2011). After implantation, young children substantially expand their expressive vocabulary (Ertmer & Inniger, 2009;Majorano, Brondino, et al, 2020) and show word acquisition trajectories that are similar to those shown by children with normal hearing within the first year of life (Li et al, 2020). In some cases, this rapid vocabulary growth after implantation results in spoken abilities that are within the normative range not only by the time the children with CIs reach 10 years of age but also after only a few years of CI use (Cuda et al, 2014;Guerzoni et al, 2016;Murri et al 2015;Nicholas & Geers, 2007Niparko et al, 2010).…”
mentioning
confidence: 99%